Changes of sulfur forms in coal after tetrachloroethylene extraction and theirs transformations during pyrolysis. (15th December 2016) - Wang, Meijun; Jia, Tinghao; Wang, Jiancheng; Hu, Yongfeng; Liu, Fenrong; Wang, Hui; Chang, Liping
Highlights: Two different rank coals with high organic sulfur content were pretreated by PCE extraction. Change of sulfur forms and their transformations during pyrolysis were investigated by combined GC-FPD, Raman and XAS. Changes of sulfur forms in coals and chars before and after PCE extraction are related to the rank of coal. PCE extraction is more suitable for the desulfurization of low rank coal. The sulfur is unevenly distributed on the surface and in bulk of coal. Abstract: Two different rank coals with high organic sulfur content were selected and pretreated with tetrachloroethylene (PCE) under ultrasonic field. The effects of pretreating process on sulfur forms in two coals have been investigated by chemical analysis and sulfur K-edge X-ray absorption spectroscopy (S-XAS). The transformation behaviors of sulfur forms during pyrolysis of raw and PCE-treated coals in the fixed bed reactor with temperature-programmed apparatus were studied by gas chromatography (GC) and S-XAS. Results show that sulfur removal degree of Coal A and Coal D are 29.7% and 24.1%, respectively; and the removal of organic sulfur are dominant, accounting for 87.1% and 66.1% of total removal of sulfur from Coal A and Coal D. The sulfur compositions in coals obviously change before and after PCE extraction, and these changes appear to be unevenly distributed on the surface and in the bulk of coal. The effects of PCE extraction on the release of sulfur-containing gases are different for two coals, which are dependent on the sulfur forms in the coals, as well as the chemical structure in coals. The sulfur forms retained in the chars are significantly different for low rank Coal A before and after PCE extraction, but there is little change for high rank Coal D.